Teen Peer Educators and Diabetes Knowledge of Low-Income Fifth Grade Students. - Coleman, Karen; Clark, Andrea; Shordon, Maggie; Ocana, Leticia; Walker, Chris; Araujo, Rachel; Oratowski-Coleman, Jesica; Philis-Tsimikas, Athena (Journal of Community Health, 2011)
The current study was designed to evaluate a unique adolescent peer type 2 diabetes mellitus (Type 2 DM) prevention training program for fifth grade children. Peer educators were 22 high school students who participated in the Elementary Institute of Science's Commission on Science that Matters, a year-long program promoting active participation in the health and environmental sciences. Peer education was delivered in the form of a two hour health fair. A knowledge survey was given to fifth grade students in the classroom before the health fair began and then again in the classroom after the health fair. Fifth grade students were able to correctly identify Type 1 DM (23 vs. 40%; P < .01), Type 2 DM (21 vs. 52%; P < .001), and the signs of diabetes (10 vs. 39%; P < .001) after the health fair. This approach could be inexpensively integrated into any community-based health promotion with children and adolescents.